Effect of Simvastatin on induced apical periodontitis in rats: a tomographic and biochemical analysis - Jussara Machado PEREIRA; Alex SEMENOFF-SEGUNDO; Natalino Francisco da SILVA; Álvaro Henrique BORGES; Tereza Aparecida Delle Vedove SEMENOFF
Abstract Introduction Simvastatin is one of several statins that are used to treat hypercholesterolemia, and in dentistry, few studies have attempted to associate the administration of this compound with bone repair. Objective To evaluate the effect of simvastatin on the progression of induced apical periodontitis in rats. Material and method To this end, 36 male Wistar rats were divided into 3 groups (N=12): Induced Apical Periodontitis Associated with Simvastatin Group (APSG N=12), Induced Periodontitis Apical Induced Group (APG N=12) and Negative Control Group (CG). On the first day, APG and APSG were anesthetized, and the coronal opening of the mandibular first molar was performed. For thirty days, the APSG received 6 mg of simvastatin daily via gavage. On the thirty-first day, all groups underwent blood collection and euthanasia. The jaws were removed and fixed in formalin. CT scans were performed to measure the periapical regions. In addition, the body mass and lipid profile were analyzed. The data were subjected to statistical analysis (ANOVA and Tukey's test). Result The APG (3.42±0.65) showed the highest perimeters for the space periapical ligament, followed by APSG (1.54±0.78) and CG (0.64±0.24) (p<0.05). The lipid profile revealed the effect of simvastatin on the amount of glucose, triglycerides, HDL, and VLDL (p<0.05). Body mass APG showed the most weight gain (264.75±44.11), followed by CG (252.00±44.36) and APSG (245.41±42.56). The three groups showed significant differences in decreasing order (p<0.05). Conclusion The use of simvastatin decreased the progression of the increasing periapical ligament space in rats.